STUDI KELELAHAN MATA PADA PENGGUNA KOMPUTER DAN INTENSITAS PENERANGAN DI LAB KOMPUTER FST UIN SUNAN KALIJAGA - Muhammad Ikhwan Ardiansyah (Integrated Lab Journal, 2016)
Eyestrain on the user computer is marked by the complaints eyes during or after working at the computer. This study examines the relationship eyestrain on the user's computer in the computer lab by a factor of individual characteristics (gender and refraction of the eye) and work environment factors (light intensity). The study was conducted on 143 students who use computers in three computer labs. Measurement of eyestrain performed by questionnaire to the respondent. The results showed that there have been eyestrain experienced by 123 respondent (86 %). Pain in the neck, back and shoulders (13.4 %) is a sign of eyestrain often occur. Test statistics using chi square showed relationship between eyestrain with refraction of the eye (p-value=0.023) and eyestrain with light intensity (p-value=0.009), while the gender are not related to eye fatigue (p value = 0.344).